Plasma hormone levels in the green turtle Chelonia mydas reared under captivity as a tool to predict mating and oviposition - Rubin, Olga; Soffer, Osher; Levy, Yaniv; Aizen, Joseph (Frontiers in Marine Science, 2023)
Circulating estradiol (E2), testosterone (T) and progesterone (P4) levels, and blood chemistry were monitored in the female green turtle Chelonia mydas over continuous seasons at the Israel sea turtle breeding facility. The tested factors were analyzed with regard to the female`s nesting activity in the subsequent nesting season: Future nesters (FN) and Non-nesters (NN). Our analysis showed significant changes in all three sex steroids, E2, T, P4, and in 13 blood biochemical parameters between the two females` groups. All females presented consistent E2 profiles from year to year, with a single elevation in September in FN females. P4 levels in nesting females were high in April (mating) and higher towards the beginning of June due to oviposition, females that presented levels above 1ng/ml had successful oviposition (8 females: 1 female in 2018, 5 in 2019 and 2 in 2020). T profiles were high at the onset of vitellogenesis towards November and again high during April. We were able to predict which females would undergo oviposition with a specific profile seen only in FN females - elevated P4 levels from February to June and the elevation of metabolites electrolytes and Gamma-Glutamyl Transferase (GGT) levels toward November. This will facilitate selectively choose the mating pairs to ensure that the Mediterranean population genetic variability is maintained. Clutches per female were between 2 and 6, with 25 in total. Females laid an average of 91±7 eggs (range 39-139 eggs) per nest with emergence rate of 10% (0-58%). Overall, the same trend in circulating steroid levels was revealed over the years in the females reaching oviposition only when a certain threshold was achieved. We believe that the results observed under controlled conditions are similar to that in the wild and will contribute to breeding success, leading the way for a more effective captive breeding program to enhance the recovery of endangered species.